The concept being in the world presented by Alexander Kushner - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The originality of the subject is the usage of the category of a concept as a conceptual metaphor which is an attempt to approach the reality and a part of the author’s vision of the world. In the article the author actualizes semantic gradations of concept being in the lyrics of Alexander Kushner. The analysis shows that this concept is realized in different images and motifs, becoming the dominant of Kushner’s poetics. The semantic field of the concept includes such meanings as things/objects of the surrounding world, the artifacts of culture, (everyday) life.